Palma and Vallejo: complementarity in criticism romantic literary - Castillo Sánchez, Wellington (2020)
The purpose of this article is to show the complementarity that occurs in the romantic literary criticism between Ricardo Palma and Cesar Vallejo, two of the most important and studied Peruvian writers, being both part of the Romanticism, the first one in a fully developed way, and the second one in the last years of this movement; therefore, in different times, circumstances and particularities, but in the same interest of valuing romantic writers, we include Arnaldo Márquez, Luis Benjamín Cisneros and Carlos Augusto Salaverry, members of Palma’s bohemian group. We resort to the method of complexity, within this, the mobilization of the category of intertextuality, and the epistemological validity of the literary criticism made by both writers to find the objective evaluations, which is the purpose of this task.